Analysis of Planning System Digitalization of Non Cash Sales of Electric Equipment Companies - Widiar Onny Kurniawan; Nanda Kirana (Journal of Economics, Business, and Government Challenges, 2022)
CV Sinar Elektronik is a trading company that distributes electrical equipment like a cables, sockets, switches and etc. As a trader engaged in trading, it is important to pay attention to the information on the sales system. Sales are the main component of business processes so the exhibition can run smoothly and rhythmically. A great sales system and system will produce the right information for users. The operating system researcher conducted an analysis of the CV Sinar Elektronik distribution system and procedure which had several drawbacks and caused problems. The first problem is the lack of sales order number information and shipping information on sales orders, dust particles can be used as transaction identifiers. The second problem is that hive customers don’t have a credit limit. The last problem is the absence of a customer complaint collection system. This study to analyze and evaluate the computerized information system of the sales cycle of CV Sinar Elektronik. This type of research information is qualitative and uses kick-the-bucket information sources obtained within the company. The data collection methods used are interviews, observation and documentation. The result of this research is the design of an automated commercial information system, the improvement of the techniques and documents of the CV Sinar Elektronik.